Bimodal Trilingualism Among Deaf University Students (Spanish, Sign Language, and English): A Case Study - Vélez Negrón, Viviana M. (2026)
This study examines the grammatical proficiency in written Spanish and English —two vocal-auditory languages— of two bimodal trilingual deaf students who use a visual-gestural-spatial language, American Sign Language (ASL), and of two bilingual hearing students. It also analyzes crosslinguistic influence across languages and modalities. Participants completed (1) a demographic and linguistic background questionnaire, (2) a grammaticality-judgment test in written Spanish and English, and (3) two written narratives based on images. Results show that the deaf participants demonstrated solid grammatical performance in both vocal-auditory languages, although their outcomes are shaped by their bimodal trilingual experience. Differences between the two pairs of participants were more evident in English than in Spanish. Crosslinguistic influence was also observed, particularly among the deaf students, whose written productions reflected ongoing interaction between systems of distinct modalities. These findings provide evidence on language acquisition in bimodal trilingual contexts and highlight the need to design pedagogical and assessment practices that acknowledge linguistic plurality and promote balanced language development.